The NINDS Stroke Genetics Network: a genome-wide association study of ischemic stroke and its subtypes - Pulit, Sara L. (Lancet Neurol, 2015)
INTRODUCTION: The discovery of disease-associated loci through genome-wide association studies (GWAS) is the leading approach to the identification of novel biological pathways for human disease. To date, GWAS have had been limited by relatively small sample sizes and yielded relatively few loci associated with ischemic stroke The National Institute of Neurological Disorders Stroke Genetics Network (NINDS-SiGN) is an international consortium that has taken a systematic approach to phenotyping and produced the largest ischemic stroke GWAS to date. METHODS: In order to identify genetic loci associated with ischemic stroke, we performed a two-stage genome-wide association study. The first stage consisted of 16,851 cases with state-of-the-art phenotyping and 32,473 stroke-free controls. Cases were aged 16 to 104 years, recruited between 1989 and 2012, and subtyped by centrally trained and certified investigators using the web-based protocol, Causative Classification of Stroke (CCS). We constructed case-control strata by identify samples genotyped on (nearly) identical arrays and of similar genetic ancestral background. Data was cleaned and imputed using dense imputation reference panels generated from whole-genome sequence data. Genome-wide testing was performed within each stratum for each available phenotype, and summary level results were combined using inverse variance-weighted fixed effects meta-analysis. The second stage consisted of in silico look-ups of 1,372 SNPs in 20,941 cases and 364,736 stroke-free controls, with cases previously subtyped using the TOAST classification system according to local standards. The two stages were then jointly analyzed in a final meta-analysis. FINDINGS: We identified a novel locus at 1p13.2 near TSPAN2 associated with large artery atherosclerosis (LAA)-related stroke (stage I OR for the G allele at rs12122341 = 1·21, p = 4.50 × 10(−8); stage II OR = 1·19, p = 1·30 × 10(−9)). We also confirmed four loci robustly associated with ischemic stroke and reported in prior studies, including PITX2 and ZFHX3 for cardioembolic stroke, and HDAC9 for LAA stroke. The 12q24 locus near ALDH2, originally associated with all ischemic stroke but not with any specific subtype, exceeded genome-wide significance in the meta-analysis of small artery stroke. Other loci, including NINJ2, were not confirmed. INTERPRETATION: Our results identify a novel LAA-stroke susceptibility gene and now indicate that all loci implicated by GWAS to date are subtype specific. Follow-up studies will be necessary to determine whether the locus near TSPAN2 yields a novel therapeutic approach to stroke prevention. Given the subtype-specificity of these associations, the rich phenotyping available in SiGN is likely to prove vital for further genetic discovery in ischemic stroke. FUNDING: National Institute of Neurological Disorders and Stroke (NINDS), National Institutes of Health (NIH).